Tsiigehtchic steppe bison hair ... - Campbell, Sandy (University of Alberta Library, 2015)
This hair of a 36,500 year old bison was preserved in permafrost and found in 2007 by Shane Van Loon. It is currently on display at the Prince of Wales Northern Heritage Centre. Interpretive signs in the Museum tell us that the hair colour is similar that seen on European cave paintings of steppe bison. ...